2022
DOI: 10.3390/cancers14174069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Large Use of Combined Hypofractionated Radiotherapy in a Cohort of Anti-PD-1 Monotherapy-Treated Melanoma Patients

Abstract: To assess the role of radiotherapy in anti-PD-1-treated melanoma patients, we studied retrospectively a cohort of 206 consecutive anti-PD-1 monotherapy-treated advanced melanoma patients (59% M1c/d, 50% ≥ 3 metastasis sites, 33% ECOG PS ≥ 1, 33% > 1st line, 32% elevated serum LDH) having widely (49%) received concurrent radiotherapy, with RECIST 1.1 evaluation of radiated and non-radiated lesions. Overall (OS) and progression-free (PFS) survivals were calculated using Kaplan–Meier. Radiotherapy was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Many non-randomized report-initiated ICI and SABR concurrently with uncertainties regarding additional abscopal responses. Formenti et al, Saiag et al, and Sumodhee et al observed a 18%, 31.5% and 9.5% abscopal response rates, respectively, and a 10%, 0% and 9.5% stable disease rates, respectively (4,10,11).…”
Section: Editorial Commentarymentioning
confidence: 94%
See 1 more Smart Citation
“…Many non-randomized report-initiated ICI and SABR concurrently with uncertainties regarding additional abscopal responses. Formenti et al, Saiag et al, and Sumodhee et al observed a 18%, 31.5% and 9.5% abscopal response rates, respectively, and a 10%, 0% and 9.5% stable disease rates, respectively (4,10,11).…”
Section: Editorial Commentarymentioning
confidence: 94%
“…According to Vanpouille-Box et al the amount of cytosolic DNA which reflects the immunogenicity of tumor cells, depends on the dose per fraction ( 17 ). Interestingly, most studies that reported abscopal response used dose per fraction less than 10 Gy: 9.5 Gy for Postow et al ( 3 ), 6–9.5 Gy for Formenti et al ( 4 ), 7–8 Gy for Chicas-Sett et al ( 6 ), 6 Gy for Saiag et al ( 10 ) and Sumodhee et al ( 11 ). Of note, in these studies abscopal response was not only observed after SABR but also after conventional 3-dimensional conformal radiotherapy.…”
mentioning
confidence: 99%
“…Preclinical studies have provided evidence that the combination of radiation with ICIs can effectively stimulate systemic antitumor immunity, highlighting the rationale for the combination of immunotherapy and RT in the clinical setting [ 1 ]. Clinical trials have further demonstrated the synergistic effectiveness of combining RT with ICIs in producing significant and long-lasting clinical responses in solid tumors, particularly in patients with lung cancer and melanoma [ [16] , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%